2017
DOI: 10.13075/ijomeh.1896.00734
|View full text |Cite
|
Sign up to set email alerts
|

Chemical incidents resulted in hazardous substances releases in the context of human health hazards

Abstract: Objectives:The research purpose was to analyze data concerning chemical incidents in Poland collected in 1999Poland collected in -2009 in terms of health hazards. Material and Methods: The data was obtained, using multimodal information technology (IT) system, from chemical incidents reports prepared by rescuers at the scene. The final analysis covered sudden events associated with uncontrolled release of hazardous chemical substances or mixtures, which may potentially lead to human exposure. Releases of unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Especially acidic or basic materials, among chemical substances are particularly harmful to human body and among which, sulfuric acid is one of the major materials that cause chemical burns due to acidity [5]. As a result of analyzing 2,930 accidents that were exposed to chemical substances and had occurred in Poland from 1999 to 2009, it was found that they were exposed to more than 200 chemical substances, and especially sulfuric acid, among non-flammable corrosive liquids occupied the second highest frequency following hydrochloric acid [3]. Shin et al [2] analyzed the patients who were hospitalized to the emergency center for treating chemical damage occurred due to chemical accidents at industrial places for five years and reported that the high-frequency chemical damage-causing materials include hydrofluoric acid, compound chemicals, sulfuric acid, and magnesium in consecutive order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially acidic or basic materials, among chemical substances are particularly harmful to human body and among which, sulfuric acid is one of the major materials that cause chemical burns due to acidity [5]. As a result of analyzing 2,930 accidents that were exposed to chemical substances and had occurred in Poland from 1999 to 2009, it was found that they were exposed to more than 200 chemical substances, and especially sulfuric acid, among non-flammable corrosive liquids occupied the second highest frequency following hydrochloric acid [3]. Shin et al [2] analyzed the patients who were hospitalized to the emergency center for treating chemical damage occurred due to chemical accidents at industrial places for five years and reported that the high-frequency chemical damage-causing materials include hydrofluoric acid, compound chemicals, sulfuric acid, and magnesium in consecutive order.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is used as a material for committing a terrorist act against others in addition to hydrochloric acid, because it causes fatal damages to human body as a strong acid. According to the researches that have been conducted so far, sulfuric acid, among various chemical substances that causes chemical damage is one of the causative agents that occupy the highest frequency following the hydrofluoric acid [2,3]. However, there are very few studies on major exposure mechanism of sulfuric acid damage, area of damage, and severity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the actual inventory transfer amount of distribution department 2 is the same as the actual inventory transfer amount of distribution department 1, it can be obtained by combining (14) and (18):…”
Section: Multimodal Transport Network Model Considering Security Invementioning
confidence: 99%
“…With the update of demand information, enterprises can effectively deal with the mismatch between supply and demand through the multimodal transport logistics supply network, which can reduce inventory backlog and improve customer service level [4][5][6][7][8]. The imbalance of inventory control caused by mismatch between supply and demand can be handled by means of emergency ordering or by multimodal transport from the transshipment center [9][10][11][12][13][14][15]. The problem of emergency ordering is that the adjustment of production resources and the compression of the construction period will inevitably lead to high costs [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation